A year on, Huthis must free UN, civil society staff - Amnesty International (Amnesty International, 2025)
Huthi de facto authorities should immediately and unconditionally release dozens of staff from the UN, and Yemeni and international civil society organizations who were arbitrarily detained over the course of the past year, Amnesty International and Human Rights Watch said today.